Higher Education Reform: Challenges towards a Knowledge Society in Malaysia. - Kamogawa, Akiko (African & Asian Studies, 2003)
The Malaysian government regards highly skilled human capital as the nucleus of a knowledge-based economy and has been attempting to reform higher-educational policies in both the public and private sectors since the mid-1990s. The research reported here seeks to evaluate higher-educational policy reform as it relates to the development of human resources in an era of information and communication technologies (ICT). This research has three goals: first, to determine how Malaysian higher-educational policies have changed by looking at socioeconomic backgrounds; second, to examine case studies of the Malaysia Multimedia University (MMU), Malaysia National University (UKM), and University Malaysia Sarawak (Unimas); and third, to discuss whether ICT is affecting access and course selection in higher education in terms of gender equality. The analysis reported here concludes that the new challenges facing Malaysia offer possibilities not only for bridging the digital divide, in some aspects, nationally, but also for Malaysia to emerge as fundamental to a South-South Corporation and as a Center of Excellence internationally. It will be pointed out how, and to what extent, the government of Malaysia should reconceptualize the Malaysia Super Corridor project (MSC) in order to become a fully developed nation, equipped as a knowledge society.